Appendicular agenesis: a case report - Sedik, Alaa; Al-Dawoodi, Tarek; Elhoushy, Salwa (International Surgery Journal, 2018)
Congenital agenesis or absence of vermiform appendix is very rare. Herein, author reported a case of a 28 years old Vietnamese lady who presented with a picture of acute appendicitis. During surgery, author failed to find the appendix. Postoperatively, she made uneventful recovery and she was diagnosed as a case of nonspecific abdominal pain (NSAP) with appendicular agenesis.